On new genera and species of crack-leg spiders (Araneae, Udubidae) from Madagascar - Arnaud Henrard; Charles Griswold; Rudy Jocqué (European Journal of Taxonomy)
Two new genera, Tabiboka gen. nov. and Zorascar gen. nov., are described to accommodate five new Udubidae species from Madagascar: Tabiboka milleri gen. et sp. nov. (type species; ♂♀), T. milloti gen. et sp. nov. (♂♀), T. polotowae gen. et sp. nov. (♂♀), Zorascar pasunepipe gen. et sp. nov. (type species; ♂♀) and Z. pasunepomme gen. et sp. nov. (♀). In addition, two new species of Zorodictyna Strand, 1907 are described: Zorodictyna almae sp. nov. (♂♀) and Z. silvadavilae sp. nov. (♂♀). Uduba inhonesta Simon, 1906 is declared to be a junior synonym of Zorodictyna oswaldi (Lenz, 1891). The descriptions of the new species are complemented with a phylogenetic analysis to tentatively place them into an existing phylogenetic framework. Phylogenetic analyses based on COI and 16S rRNA genes and morphological data show that they are separate species and confirm their familial and supraspecific placement within the Udubidae. The new species are further described using high quality colored photographs, drawings, SEM and (for Zorascar gen. nov. ssp.) by the use of X-Ray micro-computed tomography to recreate virtual 3D models without destroying the original specimens. A dichotomous key to identify Malagasy Ububidae is provided. Whereas many undescribed Udubidae remain in Madagascar, the phylogenetic and generic arrangement that we present here succinctly summarizes the higher classification of Madagascar Udubidae.